2017
DOI: 10.1212/wnl.0000000000004012
|View full text |Cite
|
Sign up to set email alerts
|

Role of habenula and amygdala dysfunction in Parkinson disease patients with punding

Abstract: A breakdown of the connectivity among the crucial nodes of the reward circuit (i.e., habenula, amygdala, basal ganglia, frontal cortex) might be a contributory factor to punding in PD. This study provides potential instruments to detect and monitor punding in patients with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 34 publications
2
38
0
1
Order By: Relevance
“…Considering the subdomains of impulsivity, a positive correlation with both the thalamus and non-planning impulsivity is in line with previous findings showing a correlation between risk taking and activity in subcortical regions 58 . Likewise, the directional correlation between motor impulsivity and reduced right hippocampal volume is in line with a previous report, showing that dysfunction in this region 59,60 impacts hyperactivity and impulsivity 61 . However, careful interpretation is needed because our study was not designed to assess asymmetry or altered basal ganglia-thalamo-cortical structure in impulsivity.…”
Section: Discussionsupporting
confidence: 92%
“…Considering the subdomains of impulsivity, a positive correlation with both the thalamus and non-planning impulsivity is in line with previous findings showing a correlation between risk taking and activity in subcortical regions 58 . Likewise, the directional correlation between motor impulsivity and reduced right hippocampal volume is in line with a previous report, showing that dysfunction in this region 59,60 impacts hyperactivity and impulsivity 61 . However, careful interpretation is needed because our study was not designed to assess asymmetry or altered basal ganglia-thalamo-cortical structure in impulsivity.…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies have reported a relationship between punding and a high dose and long duration of treatment with levodopa and DAs 36,54,55 . A lack of dopaminergic terminals and intermittent levodopa administration results in abnormal dopamine release and hyperactivity of the ventral and dorsal striatal circuits, especially in D1 receptors 10,54,56 . The imbalance represented by increased connectivity in the striatum and reduced connectivity with the prefrontal cortical regions involved in the control of executive functions and directed attention may explain the purposeless repetitive behavior that occurs in punding 55,56 .…”
Section: Pundingmentioning
confidence: 99%
“…In PD patients with impulsive‐compulsive behaviors, a decreased connectivity of the frontoparietal network and a lack of increased sensorimotor functional connectivity were also observed . Additionally, a study found altered connectivity among the crucial nodes of the reward circuit in PD patients with punding (i.e., habenula, amygdala, basal ganglia, frontal cortex) …”
Section: Introductionmentioning
confidence: 99%